2006
DOI: 10.1093/jpepsy/jsl011
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Family Functioning at Mealtime: A Comparison Between Families of Children With and Without Overweight

Abstract: Self-reports and observations provide complementary information on how parents interact with their overweight children. Family-based treatment programs should include discussions on the adequate amount of parental control and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
7
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 33 publications
4
123
7
14
Order By: Relevance
“…Two cross-sectional direct observational studies examined family functioning during family meals with children who are overweight and found that families with an overweight/obese child had difficulties with managing family conflict and task accomplishment during family meals compared with families with nonoverweight children. 13,14 Findings from a pilot study, which led to the current study, suggested that more positive interpersonal interactions among family members during family meals were associated with lower BMI percentile and more healthful dietary intake in adolescents. 15 Thus, limited results suggest that family dynamics during family meals may be associated with youth weight and weight-related behaviors; however, these studies were conducted in small samples, were not racially/ ethnically or socioeconomically (SES) diverse, and included older children and adolescents.…”
Section: Ifirs-iowa Family Interaction Rating Scales Ses-socioeconomimentioning
confidence: 78%
“…Two cross-sectional direct observational studies examined family functioning during family meals with children who are overweight and found that families with an overweight/obese child had difficulties with managing family conflict and task accomplishment during family meals compared with families with nonoverweight children. 13,14 Findings from a pilot study, which led to the current study, suggested that more positive interpersonal interactions among family members during family meals were associated with lower BMI percentile and more healthful dietary intake in adolescents. 15 Thus, limited results suggest that family dynamics during family meals may be associated with youth weight and weight-related behaviors; however, these studies were conducted in small samples, were not racially/ ethnically or socioeconomically (SES) diverse, and included older children and adolescents.…”
Section: Ifirs-iowa Family Interaction Rating Scales Ses-socioeconomimentioning
confidence: 78%
“…The extant literature described many family characteristics that contribute to unhealthy eating behaviors in children and decreased success in pediatric weight management treatment, 23,[49][50][51][52][53][54] including parental control, food restriction, and unhealthy family communication. However, which characteristics predict successful treatment of pediatric obesity remains undefined, beyond the need for family support and good family communication.…”
Section: Discussionmentioning
confidence: 99%
“…It has generally been found that parents whose children are overweight or who are concerned about their children being overweight are more likely to use food restriction (e. g., Gregory, et al, 2010;Santos, et al, 2009). Indeed, in a dinnertime meal observation study parents of overweight children used restriction twice as often as parents of children who were not overweight (Moens, Braet, & Soetens, 2007).…”
Section: Restrictionmentioning
confidence: 99%